Evaluation of medical simulations. - Bewley, William L; O'Neil, Harold F (Military Medicine)
Simulations hold great promise for medical education, but not all simulations are effective, and reviews of simulation-based medical education research indicate that most evaluations of the effectiveness of medical simulations have not been of sufficient technical quality to produce trustworthy results. This article discusses issues associated with the technical quality of evaluations and methods for achieving it in evaluations of the effectiveness of medical simulations. It begins with a discussion of the criteria for technical quality, and then discusses measures available for evaluating medical simulation, approaches to scoring simulation performance, and methodological approaches. It concludes with a summary and discussion of future directions in methods and technology for evaluating medical simulations.